P494 Diagnosis and management of Lymphogranuloma Venererum (LGV) in a municipal STD clinic, san francisco, 2016–18. (14th July 2019) - Cohen, Stephanie; Brosnan, Hannah; Kohn, Robert; Bacon, Oliver; Ooms, Tamara; Nguyen, Trang
Abstract : Background: Little is known about the prevalence of lymphogranuloma venereum (LGV) among men who have sex with men (MSM) with symptomatic rectal chlamydia (CT) in US settings. Methods: Clinicians at the San Francisco municipal STD clinic order an LGV PCR when evaluating rectal symptoms on a case by case basis. The LGV PCR is only run if the CT nucleic amplification test (NAAT) is positive. We compared characteristics of MSM found to have LGV with those who were infected with non-LGV CT. Results: Rectal LGV testing was ordered at 666 patient-visits during 2016–2018, with 197 visits (29.6%) having a positive CT NAAT (169 individuals), and 94 visits a positive LGV PCR (47.7% of CT NAAT+ visits, 14.1% of all visits). Compared to visits at which the patient was CT+/LGV-, MSM with LGV were significantly (p<0.05) more likely to report rectal discharge (67% vs 40%), bleeding (39% vs 26%), have ≥=10 white blood cells (WBCs) on rectal gram stain (54% vs 29%), or be diagnosed with proctitis (78% vs 63%). At over half (54%) of CT+/LGV- visits there were < 5 WBCs on rectal gram stain, compared with 29% of CT+/LGV+ visits. There was no significant difference in reported number of sex partners, history of gonorrhea or chlamydia in the past year, or PrEP use between CT+/LGV+ and CT+/LGV- visits. MSM at CT+/LGV+ visits were more likely to be ≥ 40 years (42% vs 23%), Hispanic (40% vs 27%), and living with HIV (57% vs 30%). Conclusion: Almost 50% of MSM with rectal CT were positive for LGV in this clinic-based sample. In the absence of an LGV test, clinicians should have a low threshold for empiric LGV treatment in MSM with rectal symptoms and a positive rectal CT NAAT. Disclosure: No significant relationships.